Islam, State, and Nationalism in Brunei Darussalam, India, Indonesia, and Malaysia: A Comparative Perspective - Muh Arif Royyani; Muhammad Shobaruddin (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2019)
Islam has comprehensive roles in some aspects of human activity. It enlarged from theological aspect to political aspects. Some former colonized countries where Islam was coexisted, this religion became an embryo of nationalist movements during colonization era. This essay scrutinizes the role of Islam in escalating nationalism during colonization era and it relation with the states in post colonization era in four former colonized countries namely Brunei Darussalam, India, Indonesia, and Malaysia. By using comparative method, the essay researched some main literature (library research) related to Islam and nationalism. It was founded that Islam has significant roles in nationalist movement in the four analyzed countries through several channels. Meanwhile, in the post-independence era, the relation between Islam and state system are variably. In India, Islam is separated from state system (secular). In contrast, Islamic ideology became the main sources of state system in Brunei Darussalam (adopted entirely) and Malaysia (adopted partially). Then, Islam in Indonesia seems like “a gray zone” because the country does not using Islamic law but still adopting Islamic thoughts in several cases.